Ambidextrous Leadership and Employees' Self‐Reported Innovative Performance: The Role of Exploration and Exploitation Behaviors. (19th June 2014) - Zacher, Hannes; Robinson, Alecia J.; Rosing, Kathrin
Abstract : The ambidexterity theory of leadership for innovation proposes that leaders' opening and closing behaviors positively predict employees' exploration and exploitation behaviors, respectively. The interaction of exploration and exploitation behaviors, in turn, is assumed to influence employee innovative performance, such that innovative performance is highest when both exploration and exploitation behaviors are high. The goal of this study was to provide the first empirical test of these hypotheses at the individual employee level. Results based on self‐report data provided by 388 employees were consistent with ambidexterity theory, even after controlling for employee reports of their leaders' transformational and transactional leadership behaviors as well as employees' openness to experience, conscientiousness, and positive affect. The findings extend previous research on ambidexterity at the team and organizational levels and suggest a possible way for leaders to enhance employee self‐reported innovative performance.